1970
DOI: 10.1152/ajplegacy.1970.219.3.619
|View full text |Cite
|
Sign up to set email alerts
|

Renal autoregulation, filtration rate, and electrolyte excretion during vasodilatation

Abstract: Renal autoregulation @ration rate and electrolyte excretion during vasodilatation. Am. J. Physiol. 219(3): 619-625. 1970.-The responses of the kidney to changes in renal arterial pressure were observed before and during renal vasodilatation induced by infusion of acetylcholine or papaverine directly into the renal artery. Partial abrogation of blood flow autoregulation was produced. Glomerular filtration rate, however, continued to be autoregulated at arterial pressures between 90 and 150 mm Hg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
3

Year Published

1974
1974
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 0 publications
6
26
3
Order By: Relevance
“…These results are in agreement with the work of Johnson and Freeman (2 1), who previously suggested that systemic inhibition of NO synthase produces a pressure-dependent natriuresis. The results of study I are also consistent with previous reports of a natriuretic effect of agonists ofthe EDRF, NO, such as acetylcholine (33,34); as well as the work of Alberola et al (39) in which it was reported that, in the dog, the natriuresis and diuresis induced by extracellular volume expansion with saline was blunted during intrarenal L-NAME infusion. These previous studies suggest that stimulation of NO activity increases renal sodium excretion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in agreement with the work of Johnson and Freeman (2 1), who previously suggested that systemic inhibition of NO synthase produces a pressure-dependent natriuresis. The results of study I are also consistent with previous reports of a natriuretic effect of agonists ofthe EDRF, NO, such as acetylcholine (33,34); as well as the work of Alberola et al (39) in which it was reported that, in the dog, the natriuresis and diuresis induced by extracellular volume expansion with saline was blunted during intrarenal L-NAME infusion. These previous studies suggest that stimulation of NO activity increases renal sodium excretion.…”
Section: Discussionsupporting
confidence: 91%
“…Tolins and coworkers ( 14) recently demonstrated that the renal hemodynamic effects ofacetylcholine in vivo are also mediated by the EDRF, NO. In experimental animals acetylcholine infusion results in decreased systemic blood pressure, a large increase in glomerular capillary plasma flow, but no change in single-nephron GFR, resulting in a fall in filtration fraction (32,33). Acetylcholine infusion has also been reported to have a diuretic and natriuretic effect (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in GFR caused by papaverine has been reported by Baer et al (13). These facts suggest that there are differences in vasodilating response between CRD-401 and papaverine.…”
Section: Discussionsupporting
confidence: 56%
“…NO has been shown to increase renal blood flow, enhance glomerular filtra- tion, regulate renin release, and inhibit salt transport along the nephron (6). In vivo studies have shown that stimulation of NO generation increases (2,22,23), whereas inhibition of NO production decreases, urinary volume and Na ϩ excretion (18 -20). Moreover, impaired NO system activity has been implicated in several forms of salt-sensitive hypertension (3,13,16).…”
Section: Discussionmentioning
confidence: 99%